Faktor perilaku meningkatkan resiko keputihan - Salamah, Umi; Kusumo, Djati Wulan; Mulyana, Desi Nurlaela (Jurnal Kebidanan, 2020)
Reproductive health is a complete state of physical, mental and social well-being. Cleanliness of the female area for women is very important because it can make women feel comfortable and can prevent infectious diseases and infections. This research to determine the relationship of behavioral factors (urinary habits, use of irritants, habits during menstruation, use of underwear), and environmental factors (toilet hygiene) with the occurrence of vaginal discharge in students of the Great Achievement Midwifery Academy. This research uses analytic type with cross sectional approach. The sample of this research is 190 students of the Great Achievement Midwifery Academy, bivariate analysis using chi square. It was found that 134 (70.5%) respondents experienced vaginal discharge, there was a significant relationship between the use of irritants and vaginal discharge (p value = 0,000 and OR = 27.7), there was a significant relationship between the habit of urination and vaginal discharge (p value = 0,000 and OR = 34) , there is a significant correlation between the use of underwear with vaginal discharge (p value = 0.002 and OR = 36), there is a significant relationship between menstrual habits and vaginal discharge (p value = 0.006 and OR = 2.9). The use of irritants, urinary habits, underwear and voiding habits are risk factors for vaginal discharge.